Waterflood assessment in carbonate reservoirs - Gulnaz Moldabayeva; Jamilyam Ismailova; Alfiya Khussainova; Dinara Delikesheva; Abdulakhat Ismailov (Heliyon)
Most of the world's hydrocarbon reserves are found in carbonate rocks. Carbonate fractured reservoirs are extremely heterogeneous and difficult to study. Fractured carbonate reservoirs represent a significant challenge for efficient hydrocarbon production due to their complex dual porosity systems. This study presents a novel approach for evaluating waterflooding efficiency in such reservoirs by integrating laboratory experiments, numerical simulations using Eclipse software, and mathematical modeling based on the Warren-Root dual porosity framework. The research specifically applies this methodology to a field in Kazakhstan, providing a detailed analysis of how various fracture orientations and properties influence waterflooding performance. The study explores four scenarios of fracture arrangements and their impact on oil displacement, offering new insights into optimizing water injection strategies. The results highlight the critical role of fracture connectivity and orientation in determining the success of waterflooding operations, with findings that fractures can significantly enhance initial oil recovery but may also lead to early water breakthrough, reducing overall efficiency. The implications of this research are profound for the development and management of naturally fractured carbonate reservoirs. The novel evaluation methods and findings can guide the design of more effective field development plans, potentially improving oil recovery rates while mitigating the risks associated with waterflooding in complex geological formations. This work sets a benchmark for future studies and contributes to the ongoing advancement of reservoir management techniques.